2018
DOI: 10.1007/s00442-018-4246-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel pitcher plant–spider mutualism is dependent upon environmental resource abundance

Abstract: Positive species interactions are ubiquitous and crucial components of communities, but they are still not well incorporated into established ecological theories. The definitions of facilitation and mutualism overlap, and both are often context dependent. Many interactions that are facilitative under stressful conditions become competitive under more benign ones. This is known as the stress-gradient hypothesis, which is a specific case of context dependency. Stress can be further divided into resource and non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Some Thomisidae crab spiders, which have been documented as obligate Nepenthes pitcher-plant dwellers ( Table 1 ), have likewise been reported to assist their host plant with nitrogen acquisition. The specialised leaves of pitcher-plants, which are used to attract, trap, and digest prey [ 33 , 34 ], also provide suitable microhabitats for the crab spiders Misumenops nepenthicola and Thomisus nepenthephilus [ 34 , 35 ]. These spiders feed on visiting insects drawn to the pitcher-plants [ 34 , 36 ], and in some circumstances, the spiders increase pitcher-plant prey consumption by dropping consumed prey remains into the pitchers.…”
Section: Spider–plant Associationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some Thomisidae crab spiders, which have been documented as obligate Nepenthes pitcher-plant dwellers ( Table 1 ), have likewise been reported to assist their host plant with nitrogen acquisition. The specialised leaves of pitcher-plants, which are used to attract, trap, and digest prey [ 33 , 34 ], also provide suitable microhabitats for the crab spiders Misumenops nepenthicola and Thomisus nepenthephilus [ 34 , 35 ]. These spiders feed on visiting insects drawn to the pitcher-plants [ 34 , 36 ], and in some circumstances, the spiders increase pitcher-plant prey consumption by dropping consumed prey remains into the pitchers.…”
Section: Spider–plant Associationsmentioning
confidence: 99%
“…The specialised leaves of pitcher-plants, which are used to attract, trap, and digest prey [ 33 , 34 ], also provide suitable microhabitats for the crab spiders Misumenops nepenthicola and Thomisus nepenthephilus [ 34 , 35 ]. These spiders feed on visiting insects drawn to the pitcher-plants [ 34 , 36 ], and in some circumstances, the spiders increase pitcher-plant prey consumption by dropping consumed prey remains into the pitchers. Interestingly, two studies by Lim et al [ 34 ], and Lam and Tan [ 37 ] concluded that the type of association between crab spiders and pitcher-plants is environmentally context-dependent.…”
Section: Spider–plant Associationsmentioning
confidence: 99%
“…Chua and Lim (2012) suggested that spiders feed primarily on aquatic infauna organisms; however, we rarely observed spiders hunting for live prey such as mosquito larvae in the pitcher fluid. Recent studies point toward a neutral or even mutualistic relationship because they observed spiders ambushing pitcher visitors and dropping the carcasses into the pitcher after feeding, thereby potentially increasing the prey intake of the plant (Lam & Tan, 2019;Lim, Lam, & Tan, 2018 Bohn, H. F., & Federle, W. (2008). Harmless nectar source or deadly trap: Nepenthes pitchers are activated by rain, condensation and nectar.…”
Section: Con Cluding Remark Smentioning
confidence: 99%
“…Carnivorous plants experience additional plant–animal interactions that other angiosperms do not. These include prey–pollinator conflict where capturing potential pollinators can reduce growth and reproduction (Ellison & Gotelli, 2009), digestive mutualism where animals help carnivorous plants acquire nutrients from prey (Anderson, 2005; Anderson & Midgley, 2003; Chin, Moran, & Clarke, 2011; Ellis & Midgley, 1996; Grafe, Schöner, Kerth, Junaidl, & Schöner, 2011; Lam, Lim, Wong, & Tan, 2018; Lim, Lam, & Tan, 2018; Scharmann, Thornham, Grafe, & Federle, 2013; Schöner et al, 2017), and antagonistic plant–animal interactions such as kleptoparasitism (Burbridge, 1880; Scharmann et al, 2013).…”
Section: Introductionmentioning
confidence: 99%